EAST AFRICA’S DANGEROUS DANCE WITH THE PAST: IMPORTANT LESSONS THE NEW EAST AFRICAN COMMUNITY HAS NOT LEARNED FROM THE DEFUNCT - Joshua M. Kivuva (European Scientific Journal, ESJ, 2014)
This paper argues that while the framers of the new East African Community, cognizant of the problems of the defunct one, set out to create a new organization that would avoid the pitfalls of the old they were not bold enough to put in place legislation, institutions and processes that fully addressed them. Instead, they introduced bottlenecks that have impeded the realization of greater and faster cooperation through: 1) the creation of a complex and highly centralized decision-making process that is constrained by parochial issues of sovereignty and “zero-sum” national politics; and, 2) the reluctance by partner states to strengthen the Secretariat and other Community organs to respond to emerging issues. This notwithstanding, the Community is not yet in danger of collapse owing to important global and regional changes that make the environment for cooperation more conducive. However, if changes are not made, the community will stagnate.